A selection of relevant Portuguese children's literature published in the period of World War I - Reis da Silva, Sara (Array, 2019)
The systemic singularities of children’s literature seem to have determined the relative inconsistency of critical approaches based on historiography, where the “nodal points” are mainly of a temporal, topographical, institutional and figurative nature. One of the historical periods whose “historiographical reading” of literary outlines is incomplete and unsystematised corresponds to the timeframe between the beginning and the end of World War I. We will revisit some Portuguese authors and their works: O Navio dos Brinquedos [The Toy Ship] (1914) by António Sérgio, Era uma Vez[Once Upon a Time] (1916) by Maria Sofia Santo Tirso, and the “Polichinelo” [Punchinello] series (1918–1921) by Emília de Sousa Costa, published between 1914 and 1918, in an attempt to elucidate their technical singularities, and their most relevant ideothematic lines. Falling under the category of First Republic literature, these texts betray aesthetic sensibilities and very different ideologies, showing what was written for children and what young readers read in wartime.